الرهن الإلكتروني للعقار بالتخصيص: دراسة في قانون تنظيم الضمانات المنقولة رقم 115 لسنة 2015 - الأهواني، حسام الدين كامل (الجامعة البريطانية - كلية القانون, 2021)
صدر القانون رقم ١١٥ لسنه ٢٠١٥ بتنظيم رهن المنقولات تحت اسم قانون تنظيم الضمانات المنقولة. ويقصد به رهن المنقولات دون نقل الحيازة من المدين إلى الدائن. فالمنقولات كانت بحسب الأصل ترهن رهنا حيازيا ولم يكن من الممكن رهنها رهنا دون نقل الحيازة، لأن المنقولات متعددة لا تتناهي، على خلاف العقار الذي ينحصر وفي الأرض وما يلتصق بها اتصال قرار، كما أن المنقولات بحسب طبيعتها غير ثابتة في مكان بل تنتقل من مكان إلى آخر دون تلف. ومع التطور الهائل لتكنولوجيا المعلومات والاتصالات، والذي تمثل في موضوعنا في ظهور الحاسبات الإلكترونية وتطور الإنترنت، أصبح من الممكن التغلب على عقبات رهن المنقول دون نقل الحيازة. ونظرا لارتباط هذا الموضوع بالتطور التكنولوجي، فقد فضلنا تسميته بالرهن الإلكتروني للمنقول والذي ارتبط بالسجل الإلكتروني. ولقد أدخل المشرع العقار بالتخصيص في نطاق المنقولات التي ينطبق عليها القانون، وهو يتميز بأنه يجمع صفتين؛ وهما المنقول بالطبيعة والعقار قانونا أي بالتخصيص. وموضوع هذا البحث هو دراسة شروط وأحكام رهن العقار بالتخصيص رهنا إلكترونيا وكيف سعي المشرع للتوفيق بين الصفتين حفاظا على ضمانات الدائن. Law No. 115 of 2015 regulating movable Collateral was issued under the name of Law Regulating movables Collateral. It means mortgaging movables without transferring possession from the debtor to the creditor. The movables were, originally, mortgaged by possession and it was not possible to mortgage them without the transfer of possession because the movables are numerous and do not expire, unlike real estate, which is confined to the land and is attached to it by connection. Also, the movables, according to their nature, are not fixed in one place, but rather move from one place to another without damage. With the great development in information and communication technology, which is represented in our topic in the emergence of electronic computers and the development of the Internet, it has become possible to overcome the obstacles of mortgaging movable without transferring possession. In view of the connection of this topic with the electronic development, we preferred to call it the electronic mortgage of the movable, which is linked to the electronic record. The legislator has included within the scope of the movables covered by the law real estate by designation, and it is distinguished by the fact that it combines two characteristics, namely, movable by nature and real estate legally, i.e. by privatization. The subject of this research is a study of the terms and conditions of mortgaging real estate by privatization by electronic mortgage and how the legislator sought to reconcile the two characteristics in order to preserve the creditor's guarantees.
Keywords: القوانين والتشريعات -- الرهن الإلكتروني -- الضمانة القانونية -- قانون تنظيم الضمانة -- قانون العقارات